A COMPARATIVE CLINICAL INVESTIGATION ON LIPID-LOWERING EFFECTS OF SITAGLIPTIN AND METFORMIN IN TYPE II DIABETIC DYSLIPIDEMIA. : J Peop Univ Med Health Sci. 2025:15(2),100-106.http://doi.org/10.46536/jpumhs/2025/15.02.629 - Farzana Memon1, Ghulam Mustafa Dahri2, Muhammad Azhar Mughal3, Noureen Irum4, Nargis Pirya5, Nasrullah Aamer6 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Diabetic dyslipidemia is an imbalance of lipid profiles in diabetic patients that exacerbate higher risk of cardiovascular complications. Among anti-diabetic agents Metformin, is first-line biguanide and Sitagliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor, are widely utilized owing to its emerging and promising effects on lipid metabolism, nevertheless their comparative and combined outcomes on lipid profiles remains as a major area of investigation. The objective of our study was to evaluate the effects of Metformin as monotherapy and combination of Sitagliptin along with metformin on the lipid profile in type II diabetic patients. METHODS: This randomized, prospective controlled study was conducted involving 100 patients diagnosed with type II diabetes. The patients were divided into three treatment groups; group-I had received Sitagliptin 50 mg twice daily; group-II was administered Metformin 500 mg twice daily; and patients in group-III had received combination therapy of Sitagliptin (50 mg once daily) and Metformin (500 mg twice daily) over a period of 36-week. The blood samples were collected at baseline, 18th and 36th week analyzed for biochemical lipid parameters including total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), very-low-density lipoprotein (VLDL), and low-density lipoprotein (LDL). Statistical analysis was performed using SPSS 24.0, applying two-way ANOVA and paired t-test with level of significance set at p<0.05. RESULTS: Sitagliptin, Metformin, and their combination exhibited significant improvement in lipid profiles in Type II diabetic patients. Both anti-diabetic agents as monotherapy reduced TC, TG, VLDL, and LDL, with significant increase in HDL. Metformin demonstrated a marginally higher reduction in TC and TG levels, while Sitagliptin displayed modest but favorable outcomes. The combination treatment resulted in the most pronounced improvement in all lipid biochemical parameters, suggesting a possible synergistic effect. CONCLUSION: This study reveals that the combination of Metformin and Sitagliptin is superior in targeting diabetic dyslipidemia therefore; it may be considered a favorable option in the comprehensive management of type II diabetes.